Some Trends and Applications of Operational Research/Management Science to Operations Management - Ramón Companys Pascual; Imma Ribas (International Journal of Production Management and Engineering)
The editor suggested us to write about our point of view on the current use of Operations Research techniques applied to the Operations Management and about its future evolution. With some of unconsciousness we accept it, but it is obvious that our vision, even though we try to do our best, will be partial and biased. Hence the title chosen shows signs of prudence. More caution have been applied to the development where, after a glance at the past and reflection on the abundance of new denominations without content, we consider five aspects that, nowadays, acquire increasing importance and that will strongly influence in future developments. Among the five aspects two correspond to trends in the field of operations research techniques, one is a philosophy in the field of operations management, another to an area of the company and the last one to an industrial sector in which operations management, supported by operations research methods, is taking a predominant role.